When the law is half-baked: a critique of the new anti-sexual harassment law in Malaysia - Hamin, Zaiton; Kamaruddin, Saslina; Wan Rosli, Wan Rosalili (Faculty of Administrative Science and Policy Studies, 2023)
Before the 1955 amendment to the Employment Act, sexual harassment was not considered illegal in Malaysia. However, the amendment now requires employers to investigate any harassment or sexual harassment complaints and imposes criminal penalties for non-compliance. Unfortunately, victims of sexual harassment outside of the workplace have little legal protection under the Penal Code or the Communications and Multimedia Act 1998. Finally, in October 2022, the Anti-Sexual Harassment Act 2022 was enacted after over two decades of advocacy by women's rights groups and NGOs. However, this paper aims to critically examine the 2022 Act, which is still very new and has not been extensively studied academically. Using a qualitative research methodology, including a doctrinal and comparative legal approach and content analysis of the primary source, the 2022 Act itself, the authors argue that despite being a victim-centric law, the 2022 Act is inadequate in protecting victims of sexual harassment due to its failure to include significant provisions on the definition of sexual harassment, protection against victimisation, protection against a hostile environment, and employers' obligations to prevent and address such conduct.